Uterocervical angle or cervical length for prediction of impending preterm delivery in symptomatic patients - Reyna-Villasmil, Eduardo (2020)
Objective: To compare the uterocervical angle with the cervical length in the prediction of impending preterm delivery in symptomatic patients. Design: Case-control study. Institution: Central Hospital “Dr. Urquinaona”, Maracaibo, Venezuela. Participants: Patients with preterm delivery within 7 days (group A) and pregnant women with preterm delivery beyond 7 days (group B). Methods: At the time of diagnosis, the patients were evaluated using transvaginal ultrasound and were followed until delivery. Main outcome measures: General characteristics, uterocervical angle, cervical length, impending preterm delivery, and prognostic efficacy. Results: 326 patients were included, 75 women presented impending preterm delivery (group A) and 251 patients were considered as controls (group B). The patients in group A had significantly higher values of the uterocervical angle and lower cervical length compared to the patients in group B (p <0.0001). The uterocervical angle showed an area under the curve of 0.864, while the value of the area under the curve of cervical length was 0.985. The difference in the discrimination ability between the areas under the curve of each test was significant (p <0.0001). Conclusion: The uterocervical angle is not greater than the cervical length in predicting impending preterm delivery in symptomatic patients.